The world's oceans : geography, history, and environment - Buschmann, Rainer F.; Nolde, Lance (ABC-CLIO, 2018)
"This single-volume resource explores the five major oceans of the world, addressing current issues such as sea rise and climate change and explaining the significance of the oceans from historical, geographic, and cultural perspectives"--